High School Student Burnout: Is Empathy a Protective or Risk Factor? - Farina, Eleonora; Ornaghi, Veronica; Pepe, Alessandro; Fiorilli, Caterina; Grazzani, Ilaria (Frontiers in Psychology, 2020)
Students’ school burnout has been extensively investigated in relation to interpersonal factors such as peer relations and social adjustment. However, few studies have examined the role of personal factors such as empathic skills. Our aim in this study was to test, within a single comprehensive model, how students' empathic skills affect their levels of school burnout, both directly and indirectly via satisfaction with school relationships. A sample of 998 high school students (aged 14 to 19 years) took part in this cross-sectional study. Participants completed quantitative self-report measures of school burnout, empathic skills (both cognitive and affective), and satisfaction with school relationships (peers and teachers). Using structural equation modelling, we tested a conceptual model in which emphatic skills were hierarchically associated with satisfaction about school relationships and school burnout, while also controlling for age. The structural equation model offered an excellent fit for the empirical data. Analysis of the total, direct, and indirect effects showed that empathic skills were associated with both satisfaction about school relationships and school burnout. Satisfaction with school relationships appeared to mediate the relationship between empathy and school burnout. Students’ age was also found to have statistically significant effects. The negative effect of high school students’ empathic skills on their risk of school burnout may be prevented or at least reduced by helping them to develop positive and satisfying relationships with both teachers and peers.